Undergraduates’ challenges as predictors of their readiness for online learning during COVID-19 in Botswana - Samohembo, Bright; Baliyan, Som Pal (Journal of Education and e-Learning Research, 2024)
This quantitative study identified challenges undergraduates faced in Botswana and predicted their readiness for online learning during COVID-19. A descriptive and correlational survey research design was adopted using the Technology Acceptance Model (TAM). A questionnaire was constructed for data collection from a randomly sampled 75 agriculture undergraduates (n=75) at the Botswana University of Agriculture and Natural Resources. A one-sample t-test demonstrated that undergraduates needed to prepare for online learning. They faced several significant challenges including slow personal laptops and devices, lack of interaction between students and teachers, lack of social interaction within a class, lack of immediate feedback and interruptions in lessons, disturbances during lessons, limited broadband data and frequent technology failures. A one-way ANOVA and independent t-test revealed no age, gender and study year differences among undergraduates for the readiness and challenges. Regression analysis determined lack of interaction in class, lack of suitable infrastructure and insufficient training to use the system are the challenges that predicted undergraduates’ readiness for online learning. The preparation of undergraduates for online learning can be enhanced by improving the interaction during online lessons, developing the infrastructure required for online teaching and learning and offering training on the use of online teaching and learning systems.